L-arginine supplementation reduces mortality and improves disease outcome in mice infected with Trypanosoma cruzi - Carbajosa, Sofía (2018)
Chagas disease caused by Trypanosoma cruzi is a neglected disease that affects about 7 million people in Latin America, recently emerging on other continents due to migration. As infection in mice is characterized by depletion of plasma L-arginine, the effect on infection outcome was tested in mice with or without L-arginine supplementation and treatment with 1400W, a specific inhibitor of inducible nitric oxide synthase (iNOS). We found that levels of L-arginine and citrulline were reduced in the heart and plasma of infected mice, whereas levels of asymmetric dimethylarginine, an endogenous iNOS inhibitor, were higher. Moreover, L-arginine supplementation decreased parasitemia and heart parasite burden, improving clinical score and survival. Nitric oxide production in heart tissue and plasma was increased by L-arginine supplementation, while pharmacological inhibition of iNOS yielded an increase in parasitemia and worse clinical score. Interestingly, electrocardiograms improved in mice supplemented with L-arginine, suggesting that it modulates infection and heart function and is thus a potential biomarker of pathology. More importantly, L-arginine may be useful for treating T. cruzi infection, either alone or in combination with other antiparasitic drugs.